What Determines the Innovative Success of Subsidized Collaborative R&D Projects? – Project-Level Evidence from Germany – - Michael Schwartz; Francois Peglow; Michael Fritsch; Jutta Günther (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2010)
Systemic innovation theory emphasizes that innovations are the result of an interdependent exchange process between different organizations. This is reflected in the current paradigm in European innovation policy, which aims at the support of collaborative R&D and innovation projects bringing together science and industry. Building on a large data set using project-level evidence on 406 subsidized R&D cooperation projects, the present paper provides detailed insights on the relationship between the innovative success of R&D cooperation projects and project characteristics. Patent applications and publications are used as measures for direct outcomes of R&D projects. We also differentiate between academic-industry projects and pure inter-firm projects. Main results of negative binomial regressions are that large-firm involvement is positively related to patent applications, but not to publications. Conversely, university involvement has positive effects on project outcomes in terms of publications but not in terms of patent applications. In general, projects' funding is an important predictor of innovative success of R&D cooperation projects. No significant results are found for spatial proximity among cooperation partners and for the engagement of an applied research institute. Results are discussed with respect to the design of R&D cooperation support schemes. – – Die gegenwärtige europäische Innovationspolitik unterstreicht das systemische Verständnis von Innovationsprozessen, demzufolge Innovationen das Ergebnis interdependenter Austauschprozesse verschiedener Akteure sind. Dies spiegelt sich in einer verstärkten öffentlichen Förderung kooperativer FuE- und Innovationsvorhaben zwischen Wissenschafts- und Wirtschaftsakteuren wider. Der vorliegende Beitrag untersucht diesbezüglich den Einfluss wesentlicher Charakteristika solcher FuE-Verbundvorhaben auf deren innovativen Erfolg anhand eines Datensatzes von 406 geförderten FuEProjekten. Zur Messung des Innovationsoutputs dieser Projekte werden Patentanmeldungen und Publikationen herangezogen. Ferner wird nach Verbundprojekten zwischen Wissenschaft und Industrie und Projekten mit ausschließlich industriellen Partnern differenziert. Die Ergebnisse zeigen, dass die Einbindung von Großunternehmen einen positiven Einfluss auf Patentanmeldungen hat, nicht aber auf die Zahl der Publikationen. Die Einbindung einer Universität in ein Verbundprojekt hat positive Effekte auf die Zahl der Publikationen, nicht aber auf die Anzahl der Patentanmeldungen. Ferner lassen sich signifikant positive Effekte für die Höhe der Förderung nachweisen. Räumliche Nähe der Kooperationspartner wie auch die Einbindung eines anwendungsorientierten Forschungsinstitutes haben keinen Einfluss auf den Innovationserfolg der FuE-Kooperationsprojekte. Der Beitrag schließt mit einer Diskussion der Ergebnisse hinsichtlich der Ausgestaltung von Förderprogrammen zugunsten von FuE-Kooperationen.
urn:nbn:de:101:1-2010070649
Keywords: O31; O32; O38; 330; R&D Cooperation; Innovation; Academic-Industry-Linkages; Innovation Policy; FuE-Kooperationen; Innovationspolitik; Projekterfolg; Forschungskooperation; Forschungs- und Technologiepolitik; Innovationspolitik; Wirkungsanalyse; Patent; Publikationsanalyse; Deutschland; Sachsen